2021
DOI: 10.4103/1995-7645.318304
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin as an adjunct treatment for hospitalized adult COVID-19 patients

Abstract: Objective: To evaluate different doses of ivermectin in adult patients with mild COVID-19 and to evaluate the effect of ivermectin on mortality and clinical consequences. Methods: A randomized, double-blind, placebo-controlled, multicenter clinical trial was performed at five hospitals. A total of 180 mild hospitalized patients with COVID-19 confirmed by PCR or chest image tests were enrolled and allocated to six arms including hydroxychloroquine 200 mg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…One retrospective study reported that ivermectin reduced all-cause mortality ( 114 ), while another reported no difference in clinical outcomes or viral clearance ( 115 ). Small RCTs enrolling less than 50 patients per arm have also reported a wide array of positive ( 116 120 ) and negative results ( 121 , 122 ). A slightly larger RCT enrolling 115 patients in two arms reported inconclusive results ( 123 ).…”
Section: Disrupting Host-virus Interactionsmentioning
confidence: 99%
“…One retrospective study reported that ivermectin reduced all-cause mortality ( 114 ), while another reported no difference in clinical outcomes or viral clearance ( 115 ). Small RCTs enrolling less than 50 patients per arm have also reported a wide array of positive ( 116 120 ) and negative results ( 121 , 122 ). A slightly larger RCT enrolling 115 patients in two arms reported inconclusive results ( 123 ).…”
Section: Disrupting Host-virus Interactionsmentioning
confidence: 99%